Sufism, literary production, and printing in the nineteenth century - Chih, Rachida; Seesemann, Rüdiger; Mayeur-Jaouen, Catherine (Mitteilungen zur Sozial- und Kulturgeschichte der islamischen Welt, 2015)
"This volume unites most of the papers presented at the International conference on Sufism, Literary Production, and Printing in the Ninetheenth century, hel in Cairo in March 2010 at the IFAO and the Institut dominicain d'édudes orentales du Caire (IDEO; Dominican Institute for Oriental Studies in Cairo)"--Page IX